Enhancement of flexural performance of RC beams with steel wire rope by external strengthening technique. (3rd April 2021) - Haryanto, Yanuar; Han, Ay Lie; Hu, Hsuan-Teh; Hsiao, Fu-Pei; Hidayat, Banu Ardi; Widyaningrum, Arnie
ABSTRACT: Reinforced concrete structures around the world need repairing or strengthening at some stage in their lifetimes for different reasons. Steel wire rope is one of the potential materials to strengthen reinforced concrete structures do to its high strength, lightweight, and high flexibility properties. This research was, therefore, conducted to investigate a relatively new technique to strengthen reinforced concrete beams using external steel wire ropes. This involved testing five beam specimens under a four-point bending configuration for failure, and the strengthening effects of external wire ropes on their performance were also studied. The results showed the ultimate load capacity was also significantly enhanced up to 250% compared to the control specimen. Moreover, the stiffness and energy absorption capacity of the strengthened specimens were improved due to the external strengthening technique. This means reinforced concrete beams strengthened with external steel wire rope are capable of fulﬁlling the flexural performance required for reinforced concrete structures.